Resolution of Nusyuz Conflict on Household in Hadith Ahkam Perspective - Jannah, Miftahul; Husti, Ilyas; -, Rahma (Program Studi Hukum Keluarga Islam, 2024)
Marriage aims to create a peaceful and serene household. In domestic life, there are rights and obligations between husband and wife that must be mutually fulfilled so that the goals of marriage can be achieved. However, if one party violates their rights and obligations, that is called nusyuz. Nusyuz is essentially divided into two, nusyuz husband and nusyuz wife. The method used in this research is a qualitative method based on library research. Data collection techniques use references from various books, journals and articles. Meanwhile, the data analysis technique in this research uses data presentation and drawing conclusions. The results of the research explain that the solution to a nusyuz conflict is if the wife commits nusyuz, then the husband's actions take several stages, namely advising the wife, separating the bed, and hitting the wife with a blow that does not hurt. If it is the husband who carries out the nusyuz, then the action taken by the wife is to advise the husband, ask for ishlah (peace), and the final step is to make a complaint to the judge.